PERSEPSI DOSEN TERHADAP TINDAKAN PLAGIARISME MAHASISWA - I Gede Nyoman Arya Risaldi Dwi Nugraha; Made Hery Santosa; Anak Agung Gede Yudha Paramartha (SAGA: Journal of English Language Teaching and Applied Linguistics, 2020)
Cases of plagiarism exist universally. Although it is unacceptable, students are doing it purposively. Prior studies about students’ perception on this academic misconduct have been done extensively, while studies about lecturers’ perception with the same concern are limited. This research was done to fill this gap. The purpose of this study is to find out: (1) lecturer’s perception on students’ plagiarism and (2) solution to prevent students’ plagiarism. Two instruments were used in order to collect the data, they are plagiarism questionnaire and an interview guide. Both instruments are divided into two dimensions, namely knowledge dimension and attitude dimension. The questionnaire has 12 statements with 4 possible responses in each dimension. Meanwhile, there are 3 questions in the interview guide consisting of 1 question about knowledge dimension and 2 questions about attitude dimension. Thirty seven English as a Foreign Language (EFL) lecturer participants from institutions in Indonesia joined the survey and 5 of which were selected for the interview session. Both results of survey and interview are positive. The results implied an indication of students doing academic dishonesty.